Note on the presence of Phytolacca rugosa (Phytolaccaceae) in the flora of the Valley of Mexico - Cruz Durán, Ramiro; Jiménez Ramírez, Jaime; García Granados, Ma. Elena (Instituto de Ecología, A.C., 2003)
Phytolacca rugosa A. Braun & C. D. Bouché is reported for the flora of the Valley of Mexico. This species inhabits in secondary vegetation derived from oak forest at Cañadas de Santa Fe, near San Lorenzo Tepeaculco and at Bosques del Pedregal, Distrito Federal. Floral abnormalities similar to those reported for P. icosanda L. are also recorded in this species.